Oncogenic role of an epigenetic reader of m6A RNA modification: YTHDF1 in Merkel cell carcinoma - Orouji, Elias; Ludwig-Peitsch, Wiebke; Orouji, Azadeh; Utikal, Jochen (Cancers, 2020)
Merkel cell carcinoma is a deadly skin cancer, which in the majority of cases is caused by the Merkel cell polyomavirus (MCPyV). The viral small T antigen is regarded as the dominant oncoprotein expressed in the tumor cells. We used genomic screening of copy number aberrations along with transcriptomic analysis to investigate regions with amplification that harbor differentially expressed genes. We identified YTHDF1, a protein that is a reader of N6-methyladenosine (m6A) RNA modifications, to have high copy gains and to be highly expressed in Merkel cell carcinoma. Importantly, we identified the presence of m6A on small T antigen mRNA suggesting a relation between YTHDF1 amplification and MCPyV gene expression. Interestingly, knockdown of YTHDF1 in Merkel cell carcinoma (MCC) cell lines negatively affected the translation initiation factor eIF3 and reduced proliferation and clonogenic capacity in vitro. Furthermore, analysis of survival data revealed worse overall survival in YTHDF1high MCC patients compared to YTHDF1low patients. Our findings indicate a novel oncogenic role of YTHDF1 through m6A machinery in the tumorigenesis of MCC.
Im Titel ist die Zahl 6 hochgestellt
Gesehen am 29.04.2020